ENHANCING STUDENTS’ ACHIEVEMENT AND MOTIVATION TOWARD READING COMPREHENSION BY USING HUMOR STORY AT THE 11th GRADE OF SMK NEGERI 6 BULUKUMBA - Eryana, Surni; Nappu, Syamsiarna; Bte Abdul, Nurdevi (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2018)
The objective of the study was to find out the students’ achievement and motivation toward reading comprehension by using humor story. The researcher applied a pre-experimental design with one group pre-test and post-test design. The subject of the research was the eleventh grade of SMK Negeri 6 Bulukumba year 2017-2018. The sample consist 17 students. This research was conducted for eight meetings. The data were collected through test where humor story is one of material that usually used to find out the significance of the students achievement in reading comprehension and questionnaire test use to find out the students motivation in reading comprehension. The result of the data analysis showed that there was significant difference between pre-test and post-test. The researcher’s findings indicated that humor story was enhanced students reading comprehension in terms of interpretive comprehension. It was provided by the students’ mean score in pre-test was 5.55 and post-test 7.41. it showed that the students’ reading comprehension in post-test was higher than pre-test. The value of t-test was 9.31 and it was greater than t-table 2.120 at the level of significance (p) = 0.5 with degree of freedom (df) = N – 1 = 16 where N = 17 students. It was found that the result of t-test value was higher than the t-table (9.31>2.120). It means that the alternative Hypothesis (H1) was accepted and the Null Hypothesis (Ho) was rejected. In other words, humor story can be used to enhance students’ reading comprehension skill. Besides, students’ motivation score in reading comprehension was dominant in competition in reading were the mean score 65.25. It can be concluded that the used humor story approach was able to give greater contribution in teaching and learning reading comprehension.